Spending Behavior of Thai Tourists in Dan Sai District, Loei province, Thailand: Seemingly Unrelated Regression Estimation Analysis - NONTHAPOT, Sakkarin; WATTANAKUL, Thanet; WANGKEEREE, Kitiya (Journal of Environmental Management and Tourism, 2019)
The purpose of this study is to investigate the spending behavior of Thai tourists in Dan Sai District, Loei province, Thailand by applying the Almost Ideal Demand System (AIDS) model. The analysis was conducted by employing Seemingly Unrelated Regression Estimation (SURE). A questionnaire was used to collect data and 400 samples were collected. The results revealed that the price factor influences the cost of accommodation on other expenses, food and beverage expenses on other expenses and travel expenses on other expenses while the revenue factor influences travel costs on other expenses and the cost of souvenirs on other expenses. The results of the study show that there should be measures to stimulate tourist spending using price strategy to encourage tourists to spend more, and marketing strategies should be used to encourage high-income tourists to spend in Dan Sai District.